Occupy Waikīkī: pushing the borders of land, sea and story-telling in Kristiana Kahakauwila’s This is Paradise (2013) - Sylvie Largeaud-Ortega (Archivio Antropologico Mediterraneo)
This essay explores Kahakauwila’s short story This is Paradise from the angle of post- and decolonial studies and environmental humanities, and presents it as an ecofeminist and counterhegemonic Oceanian identitarian narrative. With special references to autochthonous antinuclear protests and claims to sovereignty (Trask, Teaiwa, Walker), it argues that female author and characters all Occupy Waikīkī, as colonials, as resistants, or as hybrid cultural agents. The beach becomes a place of Native political, environmental and cultural resistance, where American colonialism, ‘militourism’ and Globalising capitalism are being challenged. It defends the oppressed female figures from both global South and global North, metaphorically counters colonialism and restores their historical and spiritual polysemy to land, beach and ocean in Waikīkī.